Influence of fluorescencecontrolled Er:YAG laser radiation, the Vectort system and hand instruments on periodontally diseased root surfaces in vivo - F. Schwarz (journal of clinical periodontology, 2006)
Objectives: The aim of the present study was to evaluate the effects of fluorescencecontrolled Er:YAG laser radiation, an ultrasonic device or hand instruments on periodontally diseased root surfaces in vivo. Material and Methods: Seventy-two single-rooted teeth (n512 patients) were randomly treated in vivo by a single course of subgingival instrumentation using (1–3) an Er:YAG laser (ERL1: 100 mJ; ERL2: 120 mJ; ERL3: 140 mJ; 10 Hz), or (4) the Vectort ultrasonic system (VUS) or (5) hand instruments (SRP). Untreated teeth served as control (UC). Areas of residual subgingival calculus (RSC) and depth of root surface alterations were assessed histo-/morphometrically. Results: Highest values of RSC areas (%) were observed in the SRP group (12.5 6.9). ERL(1–3) (7.8 5.8, 8.6 4.5, 6.2 3.9, respectively) revealed significantly lower RSC areas than SRP. VUS (2.4 1.8) exhibited significantly lower RSC areas than SRP and ERL(1, 2). Specimens treated with SRP revealed conspicuous root surface damage, while specimens treated with ERL(1–3) and VUS exhibited a homogeneous and smooth appearance. Conclusion: Within the limits of the present study, it may be concluded that ERL and VUS enabled (i) a more effective removal of subgingival calculus and (ii) a predictable root surface preservation in comparison with SRP.